DESIGNING POLYMER COATED CARBON NANOTUBE DETECTORS FOR ALKANE VAPORS (Undergraduate Research Journal; 2017, 2017)
Alkane vapors are difficult to be detected in oil pipelines until a leak exceeds 1% of the total flow. Yet, an alkane leak can cause severe security, environmental, and human health problems if it is not identified or addressed. Detecting low concentrations of alkanes will lead to the detection of small leaks in oil pipelines. However, this requires a sensor, which can detect a substance that is inert at room temperature. Polymer coated carbon nanotubes provide that sensor. Polymers, when coating a network of carbon nanotubes, can serve as a tunnel barrier between adjacent carbon nanotubes. In a sensor, adsorption causes this barrier to swell increasing the resistance of the network. This enables the detection of charge transferred inactive species such as alkanes. In this research, design rules were applied to the polymer to make it a suitable host for alkanes by varying the functional end groups of the polymer to enable detection of specific alkanes.